Which health technologies should be funded? A prioritization framework based explicitly on value for money - Golan Ofra; Hansen Paul (BMC, 2012)
Abstract Background Deciding which health technologies to fund involves confronting some of the most difficult choices in medicine. As for other countries, the Israeli health system is faced each year with having to make these difficult decisions. The Public National Advisory Committee, known as 'the Basket Committee', selects new technologies for the basic list of health care that all Israelis are entitled to access, known as the 'health basket'. We introduce a framework for health technology prioritization based explicitly on value for money that enables the main variables considered by decision-makers to be explicitly included. Although the framework's exposition is in terms of the Basket Committee selecting new technologies for Israel's health basket, we believe that the framework would also work well for other countries. Methods Our proposed prioritization framework involves comparing four main variables for each technology: 1. Incremental benefits, including 'equity benefits', to Israel's population; 2. Incremental total cost to Israel's health system; 3. Quality of evidence; and 4. Any additional 'X-factors' not elsewhere included, such as strategic or legal factors, etc. Applying methodology from multi-criteria decision analysis, the multiple dimensions comprising the first variable are aggregated via a points system. Results The four variables are combined for each technology and compared across the technologies in the 'Value for Money (VfM) Chart'. The VfM Chart can be used to identify technologies that are good value for money, and, given a budget constraint, to select technologies that should be funded. This is demonstrated using 18 illustrative technologies. Conclusions The VfM Chart is an intuitively appealing decision-support tool for helping decision-makers to focus on the inherent tradeoffs involved in health technology prioritization. Such deliberations can be performed in a systematic and transparent fashion that can also be easily communicated to stakeholders, including the general public. Possible future research includes pilot-testing the VfM Chart using real-world data. Ideally, this would involve working with the Basket Committee. Likewise, the framework could be tested and applied by health technology prioritization agencies in other countries.